Dedicating Time to Volunteering: Values, Engagement, and Commitment to Beneficiaries. Issue 4 (7th June 2013) - Shantz, Amanda; Saksida, Tina; Alfes, Kerstin
<x xml:space="preserve">Abstract</x> A moderated mediation model was developed to explain the variation in the amount of time volunteers dedicate to their chosen voluntary cause. Data from 534 volunteers of an international aid and development agency in the United Kingdom revealed a positive relationship between prosocial values and time spent volunteering. The results also show that volunteer engagement fully mediated the relationship between the value motive and time spent volunteering, and the strength of the mediated effect varied as a function of volunteers' commitment to beneficiaries. These findings provide a new perspective on the link between volunteers' motivation and active participation in volunteer activities. Implications for practice and future research directions are discussed.